Shifting Dataset to Preserve Data Privacy - Pozi M.S.M.; Bakar A.A.; Ismail R.; Yussof S.; Rahim F.A.; Ramli R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Classification (of information); Data mining; E-learning; Large dataset; Learning systems; Classification tasks; Data attributes; Dataset shifts; Generative model; Kernel Density Estimation; Privacy preservation; Privacy preserving; Synthetic data; Data privacy